Responses of intertidal invertebrates to rising sea surface temperatures in the southeastern Indian Ocean - Wells, Fred E.; Keesing, John K.; Gagnon, Marthe Monique; Bessey, Cindy; Spilsbury, Francis; Irvine, Tennille R. (Frontiers in Marine Science, 2023)
Introduction The west coast of Western Australia (WA) is a global hotspot for increasing sea surface temperatures and marine heatwaves. Methods We used visual survey transects to compare mollusc and echinoderm populations on three coastal intertidal platform reefs on the Perth shoreline with two intertidal platforms at the west end of Rottnest Island (32°S) which are under the influence of the southward flowing Leeuwin Current. Results In 1983, temperate species dominated Perth coastal molluscan diversity, but the tropical mussel Brachidontes sculptus dominated density. Species richness on coastal platforms remained constant in 2007 and 2021, but total densities were lower in 2007 as B. sculptus declined; partial recovery occurred on coastal platforms in 2021. Tropical species were a significant component of mollusc diversity and density at Rottnest Island in 1982 and 2007. Total mollusc density declined by 98% at the island sites of Radar Reef and 86% at Cape Vlamingh and total echinoderm density by 52% and 88% respectively from 2007 to 2021; species diversity also declined sharply. Discussion Tropical species have moved southward in WA subtidal environments, but tropical, temperate and WA endemic species all suffered losses of biodiversity and catastrophic declines in density of 90% or more on the two Rottnest Island intertidal platforms. Data presented here provide a sound basis for exploring the possible causes of the catastrophic mortality at the west end of Rottnest Island and monitoring for recovery.